Indeks Pertumbuhan Larva Aedes aegypti L. Yang Terdedah Dalam Ekstrak Air Kulit Jengkol (Pithecellobium lobatum) - Firda Yanuar Pradani (Loka Litbang Kesehatan Pangandaran, 2009)
Abstracts. The control of dengue fever (DBD) vector generally use the synthetic insecticides,however it’s utilization had negative effect to the environment. Jengkol(Pithecellobium lobatum) was one of the plants which could be used as larvacidealternative because it had phenolate acid, alkaloid, terpenoid and saponin in its rind. Thisresearch was conducted to know the growth index of Aedes aegypti larvae which wassoaked in the extract of P. lobatum rind. This experiment used P. lobatum rind ekstract atconcentration 36%, 18%, 9% and 0% . The data were analyzed by using Zhang et.almethode (1993). The P. lobatum rind extract were toxic to larvae especially in first andsecond instar at concentration 17,94% respectively. Relativelly growth index range from0,817-1, it is mean that some larvae were stuned, and some were growth into the nextphase.